Saliva and serum ghrelin and obestatin in iron deficiency anemia patients - Ugur, Kader; Aydin, Suleyman; Donder, Emir; Sahin, Ibrahim; Yardim, Meltem; Kalayci, Mehmet; Sarikaya, Murat (Walter de Gruyter Gmbh, 2018)
Background: Serum ghrelin level is also associated with iron deficiency anemia (IDA), but no study has yet been published on the obestatin level in patients with IDA, even though both hormones are a single gene product. Therefore, the purpose of this investigation was to determine whether there is a link between IDA and these two hormones among other hematological parameters in patients with IDA. Methods: To measure ghrelin and obestatin, human saliva and serum were collected from 30 women with IDA and 30 control women with repeated collection of samples over a period of 1 week and 1 month. Saliva and serum ghrelin levels were measured by enzyme-linked immunosorbent assay. Results: Saliva and serum ghrelin and obestatin levels were significantly lower in the IDA group compared with controls; these levels increased slightly above baseline with iron treatment, but remained below the control values. Serum hemoglobin (Hb), ferritin and hematocrit (Hct) levels significantly increased with iron treatment, while total iron-binding capacity (TIBC) decreased compared to baseline concentrations. Conclusions: The findings suggest that IDA might be linked to imbalance of circulating (serum) and non-circulating (saliva) ghrelin and obestatin levels. Using saliva in place of serum for monitoring the two hormones should minimize inconvenience and patient discomfort.
Keywords: ghrelin; iron deficiency anemia; obestatin